Clinical correlates and prognostic impact of impaired iron storage versus impaired iron transport in an international cohort of 1821 patients with chronic heart failure. (15th September 2017) - Moliner, Pedro; Jankowska, Ewa A.; van Veldhuisen, Dirk J.; Farre, Nuria; Rozentryt, Piotr; Enjuanes, Cristina; Polonski, Lech; Meroño, Oona; Voors, Adriaan A.; Ponikowski, Piotr; Van der Meer, Peter; Comin-Colet, Josep
Abstract: Aims: To define iron deficiency in chronic heart failure (CHF), both, ferritin < 100 μg/L (indicating reduced iron storage) and transferrin saturation (TSAT) < 20% (indicating reduced iron transport) are used. The aim of the study was to evaluate clinical outcomes and prognosis of either low ferritin or low TSAT in patients with CHF. Methods and results: We evaluated the clinical impact of impaired iron storage (IIS) and impaired iron transport (IIT) either alone or in combination compared to patients with normal iron status (NIS), in an international cohort of 1821 patients with CHF with a mean age of 66 ± 13 years and mean left ventricular ejection fraction of 35% ± 15. Isolated IIS was observed in 219 patients (12%), isolated IIT in 454 (25%) and coexistence of both conditions (IIS + IIT) were seen in 389 (21%). In adjusted models we found that patients with IIS + IIT and patients with isolated IIT had higher NT-proBNP levels (OR 2.2 [1.6–3.1] and OR 2.1 [1.5–2.9] respectively) and worse quality of life (OR 1.8 [1.2–2.7] and OR 1.7 [1.2–2.5] respectively) compared with isolated IIS. Multivariate Cox analyses showed that IIS + IIT and isolated IIT were independently associated with all-cause mortality (OR 1.41 [1.06–1.86] and OR 1.47 [1.13–1.92] respectively). Patients with isolated IIS did not differ from NIS patients in terms of severity or outcomes. Conclusions: Impaired iron transport alone or in combination with impaired iron storage is associated with worse clinical profile and increased risk of mortality in patients with CHF. Patients with isolated impaired iron storage may have a milder form of iron deficiency.